1991
DOI: 10.1111/j.1439-0434.1991.tb00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Sensitivity of Rhizoctonia solani Anastomosis Groups to Fungicides

Abstract: Tolclofos-methyl, iprodione and cyproconazole, among the eleven fungicides tested in vitro, gave consistently strong inhibition against all ten anastomosis groups (AGs) of Rhizoctonia solani. Carboxin, furmecyclox, thiabendazole, fenpropimorph and vinclozolin also inhibited all AGs but with wide variations in toxicity levels (EC90 values). Pencycuron showed strong activity against four AGs but was ineffective against the other six AGs. Generally, R. solani AGs were insensitive to fenarimol and imazalil. Tolclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 24 publications
0
16
0
3
Order By: Relevance
“…Isolados pertencentes a dez grupos de anastomose de R. solani (AG1 a AG10), bem como pertencentes a Rhizoctonia spp. binucleadas, foram igualmente sensíveis a baixas concentrações de methyl-tolclophos, com valores de EC 90 inferiores a 3 ppm (Kataria et al, 1991a(Kataria et al, , 1991b. Todavia, para R. solani AG1, os autores observaram ampla variação nos valores de EC 90 a pencycuron (1 a 500 ppm), alto valor de EC 90 para benomyl (38 ppm) e baixo valor de EC 90 para iprodione (1,8 ppm).…”
Section: Fig 2 -Incidência Média De Estacas De Eucalipto (Eucalyptusunclassified
See 2 more Smart Citations
“…Isolados pertencentes a dez grupos de anastomose de R. solani (AG1 a AG10), bem como pertencentes a Rhizoctonia spp. binucleadas, foram igualmente sensíveis a baixas concentrações de methyl-tolclophos, com valores de EC 90 inferiores a 3 ppm (Kataria et al, 1991a(Kataria et al, , 1991b. Todavia, para R. solani AG1, os autores observaram ampla variação nos valores de EC 90 a pencycuron (1 a 500 ppm), alto valor de EC 90 para benomyl (38 ppm) e baixo valor de EC 90 para iprodione (1,8 ppm).…”
Section: Fig 2 -Incidência Média De Estacas De Eucalipto (Eucalyptusunclassified
“…A sensibilidade variável de Rhizoctonia spp. a pencycuron e a benomyl, pode ser explicada pelo fato de esses fungicidas terem modo de ação sítio-específica (Kataria et al, 1991a;1991b). A sensibilidade de R. solani e Rhizoctonia spp.…”
Section: Fig 2 -Incidência Média De Estacas De Eucalipto (Eucalyptusunclassified
See 1 more Smart Citation
“…12 Kataria et al reported that the sensitivities of R. solani to such fungicides as carboxin, fenarimol, fenpropimorph, imazalil and pencycuron were different in accordance with anastomosis groups. 13 However, as shown in Table 2, even the isolates in the same AG4 were separated into two groups in terms of the sensitivity to pencycuron. Further, the sensitivity of R. solani to pencycuron was found to be in negative correlation with the mycelial growth retardation at high temperature (30C), though an exceptional isolate HI 521-21 existed.…”
Section: Discussionmentioning
confidence: 99%
“…has been classified according to 14 anastomosis groups (AGs, AG-1 to AG13 and AG-BI) (Carling et al, 2002). AG is a genetic feature that results in exchange of nuclei and the combining of different genotypes (Kataria et al, 1991 andMartin, 1992).…”
Section: Resultsmentioning
confidence: 99%